2018
DOI: 10.1016/j.cmi.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic and clinical characteristics of biofilm-forming Candida parapsilosis isolates associated with fungaemia and their impact on mortality

Abstract: C. parapsilosis BF influences the clinical outcome in patients with fungaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 41 publications
6
43
1
1
Order By: Relevance
“…The studies described above show that in vitro drug susceptibility results are not clearly correlated with patient outcomes. C. parapsilosis biofilms are a major factor in outcomes for certain patients (329), particularly in the setting of infected foreign materials. In particular, C. parapsilosis is frequently associated with central venous catheters (330)(331)(332)(333).…”
Section: Antifungal Susceptibility and Resistancementioning
confidence: 99%
“…The studies described above show that in vitro drug susceptibility results are not clearly correlated with patient outcomes. C. parapsilosis biofilms are a major factor in outcomes for certain patients (329), particularly in the setting of infected foreign materials. In particular, C. parapsilosis is frequently associated with central venous catheters (330)(331)(332)(333).…”
Section: Antifungal Susceptibility and Resistancementioning
confidence: 99%
“…Candida albicans remains the most frequently isolated fungal species from catheter-associated infections followed by C. parapsilosis due to their high biofilm-forming ability (Bassetti et al 2013;Soldini et al 2018;Monfredini et al 2018). A previous study revealed that Candida biofilm production is associated with significantly higher mortality compared to patients with bloodstream infections caused by non-biofilm-forming Candida species (Rajendran et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover detached from biofilm yeast cells are important infections source. Recently it was showed that C. parapsilosis biofilm is associated with candidemia and it has an impact on mortality due to this infection [21] . Thus, it is possible to think, in the current case, C. parapsilosis firstly has formed a biofilm on CVC and next reached the blood flow being responsible by candidemia.…”
Section: Discussionmentioning
confidence: 99%